2005
DOI: 10.1038/ncb1330
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a protein transported through the secretory pathway en route to the higher plant chloroplast

Abstract: In contrast to animal and fungal cells, green plant cells contain one or multiple chloroplasts, the organelle(s) in which photosynthetic reactions take place. Chloroplasts are believed to have originated from an endosymbiotic event and contain DNA that codes for some of their proteins. Most chloroplast proteins are encoded by the nuclear genome and imported with the help of sorting signals that are intrinsic parts of the polypeptides. Here, we show that a chloroplast-located protein in higher plants takes an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
256
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(264 citation statements)
references
References 36 publications
5
256
0
1
Order By: Relevance
“…These proteins appear to use a targeting mechanism that involves the ER/secretory pathway. Carbonic anhydrase 1 (CAH1) is one of the very few higher plant proteins also known to target chloroplast through the endomembrane system 49 . However, CAH1 localizes to the stroma indicating its targeting mechanism must be different from AZI1, at least in part.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins appear to use a targeting mechanism that involves the ER/secretory pathway. Carbonic anhydrase 1 (CAH1) is one of the very few higher plant proteins also known to target chloroplast through the endomembrane system 49 . However, CAH1 localizes to the stroma indicating its targeting mechanism must be different from AZI1, at least in part.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Hu et al (2010) presented evidence showing high expression of bCA2 and bCA4 in mesophyll cells, whereas bCA3 had very low expression in mesophyll cells, while Wang et al (2014) reported very low bCA3 expression in leaves with promoter::GUS studies. Since the other CAs that show significant expression are either in the chloroplast (Fett and Coleman, 1994;Villarejo et al, 2005;Fabre et al, 2007;Burén et al, 2011;Hu et al, 2015) or mitochondria (Fabre et al, 2007;Jiang et al, 2014), we conclude that bCA2 and bCA4 are the most abundant CA isoforms in the cytoplasm. This contention is supported by leaf RNAseq data (Table I), GUS staining (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis has eight aCA genes, but only aCA1, aCA2, and aCA3 appear to be expressed in leaf tissue. aCA1 has been reported to be localized to the chloroplast in leaf tissue (Villarejo et al, 2005;Burén et al, 2011). The expression of aCA2 and aCA3 is quite low but higher than that of aCA4 to aCA8.…”
mentioning
confidence: 99%
“…Additionally, there is evidence that some proteins can also traffic to the chloroplast from the Golgi (Villarejo et al, 2005;Kitajima et al, 2009) or ER (J.K.C. Rose and S.-J.…”
Section: How Do Proteins Reach the Plant Cell Wall?mentioning
confidence: 99%